Analisis Resiko Kecelakaan Kerja dengan Metode Hazard And Operability (HAZOP) pada Departement Electrical PT XYZ - Ramdani, Ramdani; Widarman, Agung; Yudha, Haris Sandi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational safety in the basic chemical industry is a major concern, especially in the Electrical Department of PT XYZ, which has a high risk of work-related accidents. This study aims to identify potential hazards, assess risk levels, and provide corrective recommendations using the Hazard and Operability Study (HAZOP) method. Data were collected through field observations, interviews, and analysis of 37 accident cases that occurred throughout 2024. The findings revealed 20 sources of hazards, several of which were classified as extreme risks, such as arc flashes, oxygen deficiency, and capacitor explosions. Risk assessments were conducted using a 5x5 matrix based on likelihood and severity levels. The recommended control measures include engineering modifications, administrative controls, and the use of personal protective equipment. This research is expected to enhance workplace safety systems and prevent future accidents.